Finite element analysis of a free-standing concrete sea-wall as alternative to traditional land reclamation - Harris, Raymond (2018)
Singapore, a city-state home to 5.6 million population continues to grow as it strives to keep its competitive edge and sustain its economic development. One key area of development in Singapore is through the creation of new land to satisfy the demand on land use in Singapore, commonly known as land reclamation. Having been practiced for decades, this technique of dumping sand or fill materials into the designated reclaimed area until an area of usable land emerges from the sea has successfully increased Singapore’s size by 20%. Now with the increasing cost of sand fill materials due to scarcity, the conventional method of land reclamation is becoming less feasible. Thus, the solution would be to implement an alternative method of land reclamation that eliminates the need for sand infill. For this solution to have a practical implementation, an investigation into the feasibility of this method is carried out using Finite Element Method (FEM) software PLAXIS 2D & 3D. To replicate the real-life application of the method, the analysis is carried out using soil parameters derived from seabed offshore of Tuas. Furthermore, a 3D caisson seawall model is used in the analysis so that the stiffness of the cellulated structure can be properly accounted for. The caisson seawall spans 40 m long to 28 m wide. It is connected on its longer side continuously so that it forms a wall barrier in which 20 m of seawater level will be drained from the usable side. Analysis is made to determine the stability of the caisson seawall embedded at three depths: 40 m, 20 m, and 15 m. The focus of this study is to analyze the stability of caisson seawall with 15-meter embedment depth. The data obtained from the 40-m and 20-m embedment depth are used to compare the effects of embedment on the stability. With the increase in embedment depth, higher normal stress is experienced by the walls near the base. Lateral and vertical displacements of the seawall are analyzed. Results show that the displacement values are the most critical at 15 meters wall embedment, however the maximum displacement does not exceed 19 mm, which is not an issue relative to the size of the walls. As the wall is pushed towards the land side by the 20-meter water pressure, rotational movement is also present about the toe, which is an effect of the soil heaving near the landward surface. With a difference in total head of 20 meters, seepage flow is not as large as anticipated. Due to the low permeability of the surrounding clay layers, maximum discharge is not more than 0.1 m3/day/m. With the presence of sand seam layer beneath the base of the wall however, the discharge into the reclaimed area becomes 0.6 m3/day/m. Results from the preliminary material cost analysis have shown that the usage of free-standing caisson seawall is more economical compared to the land reclamation method used in Tuas Finger 2. Major cost components were also identified as the economic feasibility of the construction project depends on the interaction and contribution of all cost components.